Selective Detection of Hg2+ Ions with Boron Dipyrromethene‐Based Fluorescent Probes Appended with a Bis(1, 2, 3‐triazole)amino Receptor. Issue 7 (6th March 2019) - Shi, Wen‐Jing; Liu, Jian‐Yong; Lo, Pui‐Chi; Ng, Dennis K. P.
Abstract: By using a copper‐promoted alkyne–azide cycloaddition reaction, two boron dipyrromethene (BODIPY) derivatives bearing a bis(1, 2, 3‐triazole)amino receptor at the meso position were prepared and characterized. For the analogue with two terminal triethylene glycol chains, the fluorescence emission at 509 nm responded selectively toward Hg 2+ ions, which greatly increased the fluorescence quantum yield from 0.003 to 0.25 as a result of inhibition of the photoinduced electron transfer (PET) process. By introducing two additional rhodamine moieties at the termini, the resulting conjugate could also detect Hg 2+ ions in a highly selective manner. Upon excitation at the BODIPY core, the fluorescence emission of rhodamine at 580 nm was observed and the intensity increased substantially upon addition of Hg 2+ ions due to inhibition of the PET process followed by highly efficient fluorescence resonance energy transfer (FRET) from the BODIPY core to the rhodamine moieties. The Hg 2+ ‐responsive fluorescence change of these two probes could be easily seen with the naked eye. The binding stoichiometry between the probes and Hg 2+ ions in CH3 CN was determined to be 1:2 by Job′s plot analysis and 1 H NMR titration, and the binding constants were found to be (1.2±0.1)×10 11  m −2 and (1.3±0.3)×10 10  m −2, respectively. The overall results suggest that these two BODIPY derivatives can serve as highly selective fluorescent probes for Hg 2+ ions. The rhodamine derivative makes use of a combined PET‐FRET sensing mechanism which can greatly increase the sensitivity of detection. Abstract : PET‐FRET project : Two click‐derived BODIPY derivatives bearing a bis(1, 2, 3‐triazole)amino receptor have been prepared and investigated for their Hg 2+ ‐sensing properties. Upon binding with Hg 2+ ions, a strong emission was observed due to inhibition of the photoinduced electron transfer (PET) process in the BODIPY core or coupling with fluorescence resonance energy transfer (FRET) from the excited BODIPY core to the rhodamine moieties, resulting in a large Stokes shift.